Hematopoietic stem cells: self-renewal and expansion. Issue 4 (July 2019) - Li, Zhenrui; He, Xi C.; Li, Linheng
Abstract : N/A: Hematopoietic stem cells (HSCs) are a unique population of cells with the remarkable ability to replenish themselves through self-renewal and to give rise to differentiated cell lineages. Though having been discovered more than 50 years ago, and having been widely used in bone marrow transplantation to treat blood disorders including leukemia, expansion of HSCs remains an unmet task, thus affecting its more effective usage in clinical practice. Purpose of review: The purpose of this review article is to summarize past efforts in ex-vivo HSC expansion and to compare recent advances in expanding murine and human HSCs by targeting the N 6 -methyladenosine (m 6 A) pathway. Recent findings: Unlike past many efforts that mainly target single or limited pathways and often lead to lineage bias or expansion of progenitor cells or limited long-term HSCs (LT-HSCs), the blocking the degradation of m 6 A pathway has an advantage of stabilizing hundreds of key factors required for maintaining HSCs, thus resulting in expansion of functional LT-HSCs. Summary: The new approach of targeting the m 6 A pathway has a promising application in clinical HSC-based transplantation.